The St. Thomas Way and the Medieval March of Wales: exploring place ; heritage, pilgrimage - Clarke, Catherine A. M. (Places and Spaces, Medieval to Modern, 2020)
Frontmatter -- CONTENTS -- List of Illustrations -- Preface -- Contributor Biographies -- Introduction: Remaking Medieval Pilgrimage—The St. Thomas Way -- Chapter 1. Changing Roles of Pilgrimage: Retreating, Remembering, Re- enacting -- Chapter 2. In the Footsteps of the Past: Medieval Miracle Stories and the St. Thomas Way -- Chapter 3. Place, Time, and the St. Thomas Way: An Experiment in Five Itineraries -- Chapter 4. Archives as Commemoration / Pilgrimage as Interpretation: Hereford Cathedral, the St. Thomas Way, and Cantilupe 2020 -- Chapter 5. Heritage Soundscapes: Contexts and Ethics of Curatorial Expression -- Chapter 6. Reflection on the St. Thomas Way -- Chapter 7. String Theory for Beginners: The Art of Pilgrimage -- Chapter 8. Between the Sea and the Hills: On Walking the St. Thomas Way -- Index